1995
DOI: 10.1021/ie00043a018
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocracking of N-Decane over Zeolite-Supported Metal Sulfide Catalysts. 1. CaY-Supported Transition Metal Sulfides

Abstract: . (1995). Hydrocracking of n-decane over zeolite-supported metal sulfide catalysts. 1. CaY-supported transition metal sulfides. Industrial and Engineering Chemistry Research, 34(4), 1156-1165. DOI: 10.1021 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may downl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Supported on acidic materials (zeolite, silica-alumina, or alumina), the conventional hydrotreating catalysts Ni-Mo or Ni-W sulfides have generally good activity in hydroconversion of alkanes (280)(281)(282)(283)(284). Thus, Ni-Mo/USY shows an intermediate activity between that of a bifunctional Pt/HY zeolite catalyst and that of a monofunctional USY-zeolite in the hydroconversion of n-heptane.…”
Section: Other Potentially Important Catalysts For Hydroconversion Ofmentioning
confidence: 99%
“…Supported on acidic materials (zeolite, silica-alumina, or alumina), the conventional hydrotreating catalysts Ni-Mo or Ni-W sulfides have generally good activity in hydroconversion of alkanes (280)(281)(282)(283)(284). Thus, Ni-Mo/USY shows an intermediate activity between that of a bifunctional Pt/HY zeolite catalyst and that of a monofunctional USY-zeolite in the hydroconversion of n-heptane.…”
Section: Other Potentially Important Catalysts For Hydroconversion Ofmentioning
confidence: 99%
“…For example, it was found that, when the same acid support was impregnated with different transition metals to achieve the same metal-to-acid site ratio, there were notable differences in performance between the catalysts [86]. For example, it was found that, when the same acid support was impregnated with different transition metals to achieve the same metal-to-acid site ratio, there were notable differences in performance between the catalysts [86].…”
Section: ) Unsulfided Noble Metal Catalysts This Class Of Catalystsmentioning
confidence: 99%
“…The conditions of ideal HCR are approached when using catalysts with a strong HYD function. 418 Ideal HCR is reflected by a symmetric distribution of the cracked products among the carbon numbers around the mean. 419,420 The concept of an ideal HCR catalyst can be approached in practice with feed in the heavy naphtha range.…”
Section: Mechanism Of Hydrocrackingmentioning
confidence: 99%
“…A CaY zeolite that was prepared by ion exchange of an NaY zeolite was used as support for the preparation of a series of transition metal (Ni, Co, Fe, Mo, Ru, Rh, Pd, W, Re, Ir and Pt) catalysts by Welters et al 418 The catalysts were prepared by pore volume impregnation. After sulfiding, the HCR activity of the catalysts was evaluated in a microreactor at 3 MPa using n-decane as feed.…”
Section: Bifunctional Zeolitic Silica-alumina Hcr Catalystsmentioning
confidence: 99%